Usage of Internet for academic purposes on university students’ achievement: A literature review - Sumaiyah Jamaludin, Thandar Soe; Awang Kechik, Nurulhusnaa; Saidi, Sanisah; Chong, Mei Chan (Medwin Publishers, 2018)
The aim of this literature review was to evaluate the effectiveness of internet usage for academic purposes among healthrelated undergraduate students from various courses. This paper has highlighted for understanding more deeply on the effectiveness of internet usage among university students in their studies. This review found that socio economic status of students has both positive and negative significant effect on their academic achievement. Furthermore, students spend more than one hour online depended on the many factors that cause them to be online. The purposes of using the internet were varied as communication and academic search purposes. On the top of that, Google was the most used search engine and Pub Med was popular among the databases for their academic search among the students. From this literature review, it can be concluded that the students believed of using internet has improved on their academic performances but depending on the time they spent in the online internet.